New Product Development Process Used in the Consumer Product Manufacturing Units in Nepal - Sharma, Bed Nath (Journal of Nepalese Business Studies, 2006)
This study focuses the technical process steps for new product development used in the manufacturing units and indicates that feasibility report preparation practice is regular in the consumer product industry. Consultants are used to develop new products. Top level, line managers, and food technicians are the main decision taking, supervising, and controlling authorities in the product development process. Consultants and market are the main sources of new product ideas. Joint meeting among research and development (R&D), production and marketing staff and inter-communication system are perceived to be useful for co-ordination of activities. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.14-22